STRATEGI PEMASARAN PRODUK KRUPUK IKAN PADA UMKM SINAR MUTIARA DI DESA KARANG SERANG, KABUPATEN TANGERANG - Abu Naim; Helmas Septiyo Hadi; Agus Hermawan; Maman Supriyatman; Rahman Soesilo; Syamsudin Syamsudin; Zulfi Al Aziz; Siti Maesaroh (Jurnal Abdimas Bina Bangsa, 2023)
The development of micro, small and medium enterprises (MSMEs) plays an important role in driving local economic growth. In the midst of increasingly fierce business competition, effective marketing strategies are key to the success of MSMEs in marketing their products. This research aims to identify and analyse marketing strategies that can differentiate the fish crackers products of Sinar Mutiara MSMEs in Karang Serang Village, Tangerang Regency. This community service uses a qualitative approach by conducting in-depth interviews with the owner of Sinar Mutiara MSME and surveying local consumers to understand their preferences and perceptions of fish crackers. In addition, local market data and competitor information were also collected to provide a comprehensive understanding of the business environment. The PKM (Service to the communnity) results show that Sinar Mutiara MSME has several competitive advantages that can be used as a foothold for marketing strategies. Firstly, the use of high-quality fish raw materials gives an edge to the flavour of their fish crackers. Second, innovation in flavour variations and attractive packaging can attract consumers to try the products. Third, the focus on sustainability and support for local fishermen provides added value for consumers who care about socially and environmentally responsible business practices.            Recommended marketing strategies for Sinar Mutiara MSMEs include strengthening branding by maintaining product quality and designing attractive packaging. In addition, social media presence and participation in local culinary events can increase product visibility. Customer loyalty programmes and collaboration with restaurants or stalls around the area are also proposed to increase customer loyalty and expand market share